HUBUNGAN TINGKAT PENGETAHUAN TENTANG KEPUTIHAN DENGAN PERILAKU REMAJA PUTRI DALAM MENJAGA KEBERSIHAN DIRI DI DESA BANDUNG KECAMATAN KEBUMEN KABUPATEN KEBUMEN - rizqi solikhah; marsito -; nurlela - (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2010)
Fluor Albus is problem since long time for women, this problem cousin by didn’t know about fluor albus and they are think this problem is easy. Didn’t normal of fluor albus must do solusion quiqly because can be infertility, fluor albus is first problem from kanker leher rakhim and the finding can be die. It also cause phisiological and psychological depression. The objective of the research was to find out correlation between level of knowladge about fluor albus with maturity of teenager to keep clean her self In Bandung Village, Kebumen, Kebumen Regency. The design used in the research was descriptive analitic design with crosssectional approach. The data were analized by using Kendal Tau test to find out wether there was correlation between the variables, the samples of the study were 55 respondents with inclusion and exclusion criteria. Research finding showed that there was significant correlation between level of knowlwdge about fluor albus with maturity of teenager to keep clean her self In Bandung Village, Kebumen, Kebumen Regency with t-count 0,697 (p: <0,05). It could be concluded there was significant correlation between level of knowladge about fluor albus with maturity of teenager to keep clean her self In Bandung Village, Kebumen, Kebumen Regency. Keywords : Fluor albus, knowladge, personal hygiene, teenager